Lactylation-related gene AKR1A1 contributes to osteoporosis via metabolic–immune regulation: evidence from multi-omics integration, single-cell transcriptomics, and in vitro validation - Shao, Zichen; Deng, Qinqin; Cheng, Ling; Wu, Jianfeng; Sun, Weikang; Liang, Weidong; Li, Huanan (Frontiers in Immunology, 2025)
ObjectiveThis study aimed to systematically identify key differentially expressed genes (DEGs) associated with lysine lactylation in osteoporosis and to explore their potential roles in disease pathogenesis from a dual perspective of metabolic and immune regulation, thereby providing a theoretical basis for targeted therapeutic strategies.MethodsFive osteoporosis-related gene expression microarray datasets and one single-cell RNA-sequencing dataset were integrated from the GEO database. A lactylation-related gene panel comprising 1,347 genes was used to construct a screening framework. Batch effect correction, differential expression analysis, GO/KEGG enrichment, CIBERSORT-based immune infiltration, and GSEA/GSVA functional annotation were performed. A total of 113 combinations of machine learning models were applied to identify key genes. Single-cell UMAP clustering and CellChat-based intercellular communication analysis were conducted to further characterize the findings. In vitro experiments were performed using RAW264.7 macrophages treated with lactate and osteoporotic serum, and gene expression and lactylation levels were validated via qPCR, Western blot, and co-immunoprecipitation (Co-IP).ResultsA total of 37 lactylation-related DEGs were identified, mainly enriched in metabolic and inflammatory pathways. Among them, AKR1A1 was highlighted as a key feature gene through machine learning models, exhibiting elevated expression and high levels of lactylation, particularly enriched in monocytes and macrophages. CellChat analysis revealed that AKR1A1 participates in the SPP1–CD44 signaling pathway, mediating intercellular communication among immune cells. In vitro validation confirmed that AKR1A1 expression and lactylation levels were significantly upregulated under combined lactate and osteoporotic serum treatment, suggesting a synergistic enhancement effect.ConclusionAKR1A1 lactylation plays a pivotal role in the metabolic–immune regulatory axis of osteoporosis, contributing to metabolic reprogramming and immune microenvironment remodeling. Through involvement in the SPP1–CD44 signaling pathway, it mediates communication between monocytes and macrophages, and may serve as a novel biomarker and therapeutic target for early diagnosis and intervention in osteoporosis.